Experimental and Numerical Studies on Local Scour around Closely Spaced Circular Piles under the Action of Steady Current - Youxiang Lu; Zhenlu Wang; Zegao Yin; Guoxiang Wu; Bingchen Liang (Journal of Marine Science and Engineering, 2022)
Scour at coastal structures is a serious problem that causes damage to structures. Focusing on scour around typical gravity-type breakwaters, previous studies have revealed that scour is mainly caused by standing waves in the front of structures. For breakwaters, which consist of closely spaced circular piles, scour caused by flow may occupy a dominant position. In the present work, the scour caused by a small velocity intensity flow was studied using both experimental and numerical models. The experiments revealed that the scour depth around closely spaced circular piles was significantly larger than that of a single pile with the same diameter. The numerical model was verified by theoretical values of flow field and experimental values of scour topography. More detailed flow field information is described using a numerical model that can improve the understanding of scour mechanics. Both experimental and numerical models demonstrate that scour first occurs on the side of piles owing to the shrinkage effect of streamlining and then extends forward and backward. In addition, the scour mechanics change with the increase of the pile spacing.